The Wayward Bus Publicity Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Color poster of Jayne Mansfield (Camille Oakes) for the 1957 film of 'The Wayward Bus.' Digital copy only. No hard copy.